CARBONATE FORMATIONS OF KOZANI’S AREA (NW MACEDONIA, GREECE) AND SUITABILITY IN GLASS MANUFACTURE, ACID GAS REMOVAL AND METALLURGY - Νταγκουνάκη Κ.; Κασώλη-Φουρναράκη Α.; Τσιραμπίδης Α.; Σικαλίδης Κ. (Bulletin of the Geological Society of Greece, 2004)
In this paper the suitability of Kozani’s broader area carbonate formations for certain applications is studied based on their mineralogical, chemical and technological characteristics. The studied formations geotectoniccally belong to the Pelagonian zone and are represented mainly by pure limestones with few occurences of dolomites and dolomitic limestones. The studied samples represent: a) the Vermion section (formations Be and Bd), b) the Kozani section (formations Be and Bd), c) the Siatista section (formations S1 and S2) and d) the Vouhnos section (formations Bo1, Bo2 and Bo3). The insoluble residue, the organic matter, the whiteness and the mineralogical and chemical composition are studied in order to investigate the suitability of the studied carbonates for specific industrial applications. The results showed that the dolomitic formation of Vermion (Bd) is suitable for the manufacture of flat glass, while the limestone formations of Siatista (S2) and Vourinos (Bo1) as well as the dolomitic formation of Vermion (Bd) are suitable for the manufacture of container glass. The limestone formations of Siatista (S1, S2) and the dolomitic formations of Vermion (Bd) and Kozani (Kd) can be used as fluxes in the metallurgical blast furnace to produce a slag with the acid components of the ore, while the limestone formations of Siatista (S1, S2), Kozani (Kc) and Vourinos (Bo1, Bo2, Bo3) as well as the dolomitic formations of Vermion (Bd) and Kozani (Kd) are suitable for the sinter blasts. Finally, only the S2 limestone formation of Siatista can be used in the desulphurising of flue gas, as it fulfills the chemical specifications and the restrictions in whiteness.